Villous adenoma with low grade dysplasia arising from intestinal metaplasia and cystitis cystica of the bladder wall - Jennifer Vazzano; Jesse Sheldon; Anil Parwani; Shaoli Sun (Elsevier, 2021)
Villous adenomas arising within intestinal metaplasia (IM) of the urinary tract are exceedingly rare with only 20 cases reported in the literature. Histologically most cases of IM do not have cytological atypia; however, in rare cases IM can show dysplastic changes ranging from low-grade to high-grade as seen in the gastrointestinal tract. We report a case of low-grade villous adenoma, arising in a background of cystitis cystica, occurring in the bladder neck of a 48-year-old male with a history of end-stage renal disease, secondary hyperparathyroidism, and kidney stones who never used tobacco.We review and summarize the literature for villous adenomas of the bladder. Moreover, given the background of cystitis cystica in our case, we affirm the possible pathogenic association with chronic irritation of the urothelium. In addition, we discuss the diagnostic challenges associated with villous adenomas of the urinary tract.